Increased cardiac norepinephrine release in spontaneously hypertensive rats: role of presynaptic alpha-2A adrenoceptors - Zugck, Christian; Loßnitzer, Dirk; Backs, Johannes; Kristen, Arnt; Kinscherf, Ralf; Haass, Markus (Journal of hypertension, 2003)
An increased sympathoadrenergic activation is thought to contribute to the maintenance of elevated blood pressure levels in hypertension. Therefore, the regulation of cardiac presynaptic sympathetic neurotransmission was investigated in spontaneously hypertensive (SHR) and Wistar-Kyoto rats (WKY). Electrical field stimulation (1 min, 4 Hz) evoked a higher norepinephrine (NE) overflow from isolated perfused SHR than from WKY hearts (171 +/- 78 versus 111 +/- 27 nmol/g; means +/- SD, n = 7, P < 0.05). The difference in stimulation-evoked NE overflow was neither due to increased NE stores nor to a higher density of sympathetic nerve endings in SHR hearts. Furthermore, impairment of cardiac NE re-uptake was ruled out, as pharmacological inhibition of NE re-uptake by desipramine (300 nmol/l) similarly increased NE overflow from SHR (+ 54 +/- 17%) and WKY hearts (+ 59 +/- 18%). However, inhibition of presynaptic alpha-2 adrenoceptors (alpha-2R) with yohimbine (1 micromol/l) resulted in a significantly larger increase in NE overflow from WKY (+ 244 +/- 42%) than from SHR hearts (+ 162 +/- 47%, P < 0.05 versus WKY), indicating impairment of presynaptic inhibitory effect of alpha-2R in SHR. Supporting this notion, mRNA concentrations of alpha-2(A), the predominant presynaptic alpha-2R subtype, were reduced in SHR compared with WKY (738 +/- 251 versus 1468 +/- 518 mRNA molecules/10 ng, n = 7, P < 0.01), as quantified by competitive reverse transcription-polymerase chain reaction derived from left stellate ganglia. The impairment of the alpha-2R mediated presynaptic negative feedback mechanism by a reduced expression of the alpha-2R subtype A may increase cardiac net secretion of NE in SHR and could therefore contribute to their hypertensive phenotype.